Predictive factors for failure of nonsurgical management of intussusception and its in-hospital recurrence in pediatric patients: a large retrospective single-center study - Maria Klimeczek Chrapusta; Maciej Preinl; Zofia Łubniewska; Filip Procháska; Maria Gruba; Wojciech Górecki (SpringerOpen, 2024)
Abstract Background This study explores the effectiveness of ultrasonography (USG)-guided saline enema reduction for ileocecal intussusception. It investigates factors, ascertainable through physical examination, ultrasound, and medical history, that impact the success of the procedure and the likelihood of recurrence. Results Conducted at a tertiary referral center, the study included 323 pediatric cases diagnosed with intussusception between 2017 and 2023. Patient data, symptoms, signs, and outcomes were collected. Hydrostatic saline enema, performed under USG guidance, served as the primary non-operative treatment. Logistic regression models assessed the impact of clinical factors on success and recurrence rates. Out of 323 patients examined for eligibility, 184 met inclusion criteria and were analyzed. Successful reduction with saline enema was achieved in 86.7%. In-hospital recurrence occurred in 17.1%, notably higher for intussusceptions extending into the rectum (p < 0.03). Pathologic lead point was identified in 33.3% of operated cases. The study revealed a correlation between the increasing number of symptoms (p < 0.001) and reduced success rates in enema reduction, with vomiting (p < 0.02), diarrhea (p < 0.05), and peritoneal fluid (p < 0.008) negatively affecting outcomes. Symptom duration of 1-9 h (p < 0.001) and 10-24 (p < 0.01) correlated with higher success rates, but prolonged symptom duration of > 24 (p = 0.4) and 48-72 (p = 0.2) hours did not decrease chances for successful reduction. Conclusions Prolonged symptom duration of over 24 and 48-72 h should not be a definitive contraindication for non-operative treatment. Cumulation of symptoms typical for intussusception might reduce the chances of success. These findings contribute valuable insights into optimizing non-operative strategies for managing pediatric intussusception.